Street dreams - Kellerman, Faye. (London : Headline, 2004)
LAPD officer Cindy Becker and her police detective father struggle to get past their personal differences while searching for the mother of an abandoned newborn.
Adult.
Adult
Keywords: Abandoned children -- Fiction; Decker, Peter (Fictitious character) -- Fiction; Lazarus, Rina (Fictitious character) -- Fiction; Police spouses -- Fiction; Police -- California -- Los Angeles -- Fiction; Policewomen -- Fiction; Abandoned children -- Fiction; Decker, Peter (Fictional character) -- Fiction; Husbands -- Fiction; Lazarus, Rina (Fictional character) -- Fiction; Mystery fiction; Police -- Los Angeles (Calif.) -- Fiction; Policewomen -- Fiction; Wives -- Fiction; Los Angeles (Calif.) -- Fiction; Los Angeles (Calif.) -- Fiction; Mystery fiction